Therapeutic effect and mechanism of Anemarrhenae Rhizoma on Alzheimer’s disease based on multi-platform metabolomics analyses - Wang, Hui; Dai, Jian-Ying; He, Yu-Zhen; Xia, Zhe-Wei; Chen, Xiao-Fei; Hong, Zhan-Ying; Chai, Yi-Feng (Frontiers in Pharmacology, 2022)
Anemarrhenae Rhizoma (AR) has multiple pharmacological activities to prevent and treat Alzheimer’s disease (AD). However, the effect and its molecular mechanism are not elucidated clear. This study aims to evaluate AR's therapeutic effect and mechanism on AD model rats induced by D-galactose and AlCl3 with serum metabolomics. Behavior study, histopathological observations, and biochemical analyses were applied in the AD model assessment. Gas chromatography-mass spectrometry (GC-MS) and liquid chromatography-mass spectrometry (LC-QTOF/MS) were combined with multivariate statistical analysis to identify potential biomarkers of AD and evaluate the therapeutic effect of AR on AD from the perspective of metabolomics. A total of 49 biomarkers associated with the AD model were identified by metabolomics, and pathway analysis was performed to obtain the metabolic pathways closely related to the model. With the pre-treatment of AR, 31 metabolites in the serum of AD model rats were significantly affected by AR compared with the AD model group. The regulated metabolites affected by AR were involved in the pathway of arginine biosynthesis, arginine and proline metabolism, ether lipid metabolism, glutathione metabolism, primary bile acid biosynthesis, and steroid biosynthesis. These multi-platform metabolomics analyses were in accord with the results of behavior study, histopathological observations, and biochemical analyses. This study explored the therapeutic mechanism of AR based on multi-platform metabolomics analyses and provided a scientific basis for the application of AR in the prevention and treatment of AD.